Uso da terceira e quinta dimensão do BIM na compatibilização de projetos e geração de quantitativos - Gonçalves, Maria Isadora Messias Bezerra (Universidade Federal Rural do Semi-Árido, 2020)
With the most robust technological and architectural advances, it is essential to use tools that solve more confident problems in the design process and in the phases of the work, since more common software, such as CAD, were no longer used as only as electronic drawing board and did not add real information to the construction model. Therefore, the BIM technology presents as a differential both in the project execution process, since the English tools enable the creation or the real model in a virtual way, such as the construction phase, the execution of schedules and the most complete budgets and the tests. However, despite the various benefits, a technology is still not widespread in some countries and many professionals do not use everything that the software brings. Thus, the present work has as its theme the use of the third and fifth dimension of BIM in the compatibility of projects and generation of quantitative. None of which main objective is to approach themes about BIM and its growth in Brazil and in the world, as well as to make a practical application with the accomplishment of complementary and architectural projects using Revit, one of the most complete and currently used software in the construction sector. civilian. In this way, the work brings a practical application of one of the biggest advantages of BIM, a 3D response, for compatibility of several projects and, thus, to be able to analyze interferences more effectively, leading to more dangerous project work.
Keywords: Autodesk Revit; Building Information Modeling; Orçamento; Budget; ENGENHARIAS::ENGENHARIA CIVIL